Kauzalita a konečný automat - Bokr, Josef (International Society for Science and Engineering, o.s., 2018)
Článek se zabývá vztahem mezi podmíněnou pravděpodobností, materiální implikací a příčinností a věnuje se kauzalitě stavových přechodů v konečném automatu. Příčinností v konečném automatu se stávající literatura nezabývá.

This paper is engaged in a relationship between the conditional probability, material implication and causality and is concerned with especially the causality of states transitions into a finite automaton. No present literature deals with causality of finite automata, unfortunately.
Causality and finite automaton